Analisis Kualitas Air Sungai Kendilo Berdasarkan Metode Indeks Pencemaran - Rina Ratna Sari AR; Nurhasanah Nurhasanah; Sodikin Sodikin (Universitas Nahdlatul Ulama Blitar, 2026)
The Kendilo River is an important water source in Paser Regency, used for domestic, agricultural, industrial, and raw water needs. The Kendilo River experiences pressure from anthropogenic activities that cause pollution. This study aims to analyze the quality status and trends of the Kendilo River's water quality for the period 2019-2024. The method used is quantitative descriptive with secondary data from water quality monitoring from nine monitoring points representing the upstream, middle, and downstream segments of the river. The assessment of water quality status was carried out using the Pollution Index based on Class II water quality standards in accordance with Government Regulation Number 22 of 2021. The variables analyzed were pH, dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, total suspended solids, total dissolved solids, ammonia, nitrate, total phosphate, and fecal coliform. The results showed that the water quality status of the Kendilo River was generally classified as lightly polluted. The pollution index value increased in the period 2019-2021, then showed an improving trend until 2024, although not evenly distributed across all monitoring points. Total suspended solids were the most dominant and consistent primary pollutant. Furthermore, increases in organic load were indicated by biochemical oxygen demand, chemical oxygen demand, and total phosphate. The study's conclusions underscore the need for integrated and sustainable water quality management of the Kendilo River to prevent further degradation and maintain the river's function for the environment and community.